2016
DOI: 10.1016/j.physbeh.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in ear temperature in relation to separation distress in dogs

Abstract: Highlights• Pet dogs were tested in a brief separation test and filmed remotely using thermography• Temperature was analyzed from selected patches of both ear pinnae simultaneously• Social isolation was associated with a significant decrease in ear pinnae temperature• Temperature of the two ears did not differ significantly from each other• Long distance thermography is a useful tool in non-invasive stress monitoring AbstractInfrared thermography can visualize changes in body surface temperature that result fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 49 publications
(79 reference statements)
2
46
0
1
Order By: Relevance
“…Some dogs may also show aversive behaviour toward camera. Ogata et al, 2006;Part et al, 2014;Vainionpää, 2014;Nääs et al, 2014;Redaelli et al, 2014;Travain et al, 2015;Proctor and Carder, 2015;Telkänranta et al, 2016;Whitham and Miller, 2016;Riemer et al, 2016 Immune function (IgA/ antibody and WBC levels)…”
Section: Requires Special Equipmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Some dogs may also show aversive behaviour toward camera. Ogata et al, 2006;Part et al, 2014;Vainionpää, 2014;Nääs et al, 2014;Redaelli et al, 2014;Travain et al, 2015;Proctor and Carder, 2015;Telkänranta et al, 2016;Whitham and Miller, 2016;Riemer et al, 2016 Immune function (IgA/ antibody and WBC levels)…”
Section: Requires Special Equipmentmentioning
confidence: 99%
“…In contrast, Part et al (2014) found that dogs who were moved to kennels from a home environment had no difference in their core temperatures (measured with a thermometer in the ear canal), but they did have significantly lower surface temperatures, as measured using an infrared camera recording nose temperature. Similarly, Riemer et al (2016) used an infrared camera to measure surface temperature, specifically the temperature of the ear pinnae from long distances (6-8 m). Although this was a small sample (six dogs), the results showed that peripheral temperature decreased in response to separation and increased again upon reunion with the owner.…”
Section: Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…29 Infrared thermal imaging (IRT) has emerged as a promising tool for studying animal behaviour. 30 For instance, research employing this methodology has helped cast light on affective processing 31 in a variety of species, including macaques (Macaca mulatta) (Nakayama et al 2005;Kuraoka 32 and Nakamura 2011; Ioannou et al 2015), chimpanzees (Pan troglodytes) (Kano et al 2016; 33 Dezecache et al 2017) or dogs (Canis lupus familiaris) (Travain et al 2015;Riemer et al 2016; 34 Travain et al 2016). In these studies, IRT was deployed to detect changes in emissivity of the 35 skin caused by shifts in blood flow at body surface, a physiological process controlled by the 36 autonomic nervous system (see Ioannou et al 2014 for a comprehensive review).…”
Section: Introductionmentioning
confidence: 99%